Kinetic of Microalgae Chlorella sp. in Domestic Waste Treatment Using Oxidation Ditch Algae Reactor (ODAR) - Nabilla Candrahanifa; Nicken Elok Arohmah; Euis Nurul Hidayah; Okik Hendrianto Cahyonugroho (Nusantara Science and Technology Proceedings)
Chlorella sp is a species of green algae that can’t have the ability to move. Chlorella sp is a biofilter that removes nutrients and pollutants in wastewater. Chlorella sp also functions as a catalyst in the photosynthesis process, because there is a lot of chlorophyll. In this research, domestic waste was used as an experimental medium. Before running the oxidation ditch reactor, microalgae cultivation was carried out to increase the number of microalgae needed for research. Then the microalgae acclimatization was carried out to determine the maximum acceptable limit for the microalgae Chlorella sp. The oxidation ditch reactor has a capacity of 250 liters and is used in conditions of 60 rpm oxic and 60 rpm oxic-anoxic, and sampling is carried out every day for 5 days. This research was conducted to determine the role and effectiveness of Chlorella Sp. in degrading NO3- and PO43- content in domestic wastewater treatment. From the research results, it can be seen that the microalgae Chlorella Sp. was able to remove the maximum nitrate of 81,96% with an initial nitrate 5,82 mg/L to 1,05 mg/L. In addition, the microalgae Chlorella Sp. was also able to remove maximum phosphate of 82,09% with an initial phosphate value of 2,72 mg/L to 0,6 mg/L.